A Social Design Approach: Enhancement of Local Social Dialogue on the Transformation of Work by Digital Technology - Galey, Louis; Terquem, Valerie; Barcellini, Flore (Relations industrielles / Industrial Relations, 2022)
SummaryThe world of work is undergoing major transformations (teleworking, new technologies, Industry 4.0, social reform in some countries) in which labour relations are likely to play a central role. In this context, our case study presents an alternative approach to local social dialogue: “Social Design.” The specific aim was to mobilize stakeholders to deal with the introduction of digital technology at a large industrial company in France. Within the theoretical and methodological framework of activity-centred ergonomics, we analyzed the process of co-design and the process of design “in use.” We conducted interviews, work activity observations and simulations of future working conditions. We identified “fruitful possibilities” (e.g., more extensive participation by stakeholders and collective discussions about the transformation of work) and “real-life resistance” (e.g., difficulties in finding common agreement). We report on the quality of local social dialogue and provide an epistemology of the action of social dialogue on the theme of the transformation of work. In sum, we describe an original initiative to transform local social dialogue in the context of a changing workplace.AbstractWe present the results of a research-action initiative to strengthen participation by social dialogue stakeholders (union representatives, managers and workers) in companies that are being digitally transformed. For this, we used activity-centred ergonomics. After presenting a co-design process, i.e., “Social Design,” we describe how the initiative was carried out in a large industrial company and how it was re-designed “in use.” We thus helped certain union representatives participate in dialogue on the topical issue of digital transformation, thereby helping define a new organizational structure in the workplace and further developing the “Social Design” approach.